Inhibition of basal transcription by poliovirus: a virus- encoded protease (3Cpro) inhibits formation of TBP-TATA box complex in vitro. - Yalamanchili, P (1996)
Host cell RNA polymerase II (pol II)-mediated transcription is inhibited by poliovirus infection. We demonstrate here that both TATA- and initiator-mediated basal transcription is inhibited in extracts prepared from poliovirus-infected HeLa cells. This inhibition can be reproduced by incubation of uninfected HeLa cell extracts with purified, recombinant poliovirus protease, 3Cpro. Transient-transfection assays demonstrate that 3Cpro, in the absence of other viral proteins, is able to inhibit cellular pol II-mediated transcription in vivo. Three lines of evidence suggest that inactivation of TATA-binding protein (TBP) is the major cause of inhibition of basal transcription by poliovirus. First, RNA pol II transcription in poliovirus-infected cell extract is fully restored by bacterially expressed TBP. Second, addition of purified TBP restores transcription in heat-treated nuclear extracts from mock- and virus-infected cells to identical levels. Finally, using a gel mobility shift assay, we demonstrate that incubation of TBP with the viral protease (3Cpro) inhibits its ability to bind TATA sequence in vitro. These results suggest that inhibition of pol II transcription in mammalian cells infected with poliovirus is, at least in part, due to the inability of modified TBP to bind pol II promoter sequences.